2019
DOI: 10.1007/s10552-019-01202-1
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review on socioeconomic deprivation and survival in endometrial cancer

Abstract: Purpose The primary objectives in this review were to (1) assess the association between socioeconomic deprivation and survival in endometrial cancer patients (2) investigate if there is an association between socioeconomic deprivation and peri-operative morbidity in endometrial cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…The aim of this study was to determine the relationship between socioeconomic deprivation and survival in endometrial cancer patients in more detail. We recently published a systematic review about socioeconomic deprivation and survival in endometrial cancer patients, showing deprivation seems to be associated with worse survival, however the impact of important confounders such as BMI, smoking and comorbidities were unclear and therefore should be assessed [8]. In this study we found an association between socioeconomic deprivation and overall survival in endometrial cancer patients, with better survival for the least deprived patients in type 1 endometrial cancer.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The aim of this study was to determine the relationship between socioeconomic deprivation and survival in endometrial cancer patients in more detail. We recently published a systematic review about socioeconomic deprivation and survival in endometrial cancer patients, showing deprivation seems to be associated with worse survival, however the impact of important confounders such as BMI, smoking and comorbidities were unclear and therefore should be assessed [8]. In this study we found an association between socioeconomic deprivation and overall survival in endometrial cancer patients, with better survival for the least deprived patients in type 1 endometrial cancer.…”
Section: Discussionmentioning
confidence: 56%
“…For most types of cancer, socioeconomic deprivation is associated with survival, with more deprived patients showing poorer survival [7]. A recent systematic review showed that socioeconomic deprivation was associated with poorer survival in endometrial cancer patients, even after adjusting for stage at diagnosis [8]. However, not only stage at diagnosis is associated with worse survival, but grade of disease, obesity and comorbidities are also related to survival [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Few studies have examined the role of SES on endometrial cancer survival outcomes, 13 and only three have been based in the UK 14,15,27 . Gildea and colleagues found no association between 30‐day postoperative mortality and income deprivation, but failed to assess long‐term outcomes 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Disparities in survival by social class have been described for most adult cancers, with patients from higher social classes having better survival outcomes than patients who are socio‐economically deprived 11,12 . Few studies have examined the role of socio‐economic deprivation on survival from endometrial cancer, however 13 . A recent systematic review identified nine studies, only two of which were based in the UK, with both failing to account for clinical factors that may confound or explain the prognostic effects of SES 14,15 .…”
Section: Introductionmentioning
confidence: 99%
“…EC accounted for ~4.8% of all cases of cancer in women between 1999 and 2006 (2). With advances in the treatment of EC, >95% of patients with localized tumors survive for 5 years following diagnosis (3)(4)(5). However, effective treatment for metastatic EC remains poor (6).…”
Section: Introductionmentioning
confidence: 99%